Investigation on substrate effect on physical characteristics of CuO- sprayed thin films suitable for photovoltaic application: Ag/ZnO:Sn (n)/CuO (p)/SnO2:F. (12th May 2022) - Ajili, Mejda; Dabbabi, Samar; Bouarissa, Nadir; Kamoun, Najoua Turki
ABSTRACT: In this paper to compare the growth and optoelectronic properties of copper oxide (CuO) materials suitable for advanced application, CuO layers were synthesized on glass and SnO2 :F). The X-ray diffraction analysis showed that CuO nanoparticles were formed in pure monoclinic structure where crystallite size decreases from 37.39 to 33.44 nm when the substrate changed, respectively, from glass to SnO2 :F/glass. This crystallite size reduction was related to the energy band gap (Eg) enlargement from 1.455 to 1.525 eV due to the quantum confinement effect. Eg values were almost equal to the theoretical one for converting solar energy into electrical energy and CuO may be used as an absorber material in photovoltaic devices. Electrical characteristics were studied using the impedance spectroscopy technique at room temperature and confirmed by the Hall Effect measurements. CuO/SnO2 :F/glass thin films have best electrical parameters and consequently the Ag/ZnO:Sn(n)/CuO(p)/SnO2 :F photocell was elaborated and its J-V characteristics were analyzed.